HIF‐1α binding to AEG‐1 promoter induced upregulated AEG‐1 expression associated with metastasis in ovarian cancer. (12th April 2017) - Zhao, Ting; Zhao, Chenyan; Zhou, Yanting; Zheng, Jing; Gao, Shujun; Lu, Yuan
Abstract: Ovarian cancer with the highest mortality rate among gynecological malignancies is one of common cancers among female cancer patients. As reported in recent years, AEG‐1 was associated with the occurrence, development, and metastasis of ovarian cancer, but the mechanisms remain unclear. In the current study, invasion capabilities of ovarian cancer OVCAR3 cells were measured by viral infection and transwell assay. Western blot analysis was used to evaluate the expression levels of β ‐catenin, E‐cadherin, MMP2, and MMP9. With qRT‐PCR analysis, AEG‐1 and HIF‐1 α gene expression were detected. We used luciferase reporter gene to measure AEG‐1 promoter activity under normoxia/hypoxia in OVCAR3 cells. Our work demonstrated that AEG‐1 significantly enhanced invasion capabilities of OVCAR3 cells and the expression levels of β ‐catenin, E‐cadherin, MMP2, and MMP9 associated with invasion capabilities of OVCAR3 cells were upregulated. Furthermore, hypoxia enhanced invasion capabilities of OVCAR3 cells and induced AEG‐1 high gene expression, which was reversed by AEG‐1 knockdown lentivirus. HIF‐1 α expression upregulation was induced in OVCAR3 cells after hypoxia. HIF‐1 α knockdown lentivirus induced downregulated expression of AEG‐1 and invasion capabilities of OVCAR3 cells were also inhibited. Wild‐type AEG‐1 promoter activity under hypoxic conditions was significantly higher than that AEG‐1 mutation under normoxic conditions in the absence of hypoxia response. Our results suggested that HIF‐1 α binds to AEG‐1 promoter to upregulate its expression, which was correlated with metastasis in ovarian cancer by inducing the expression of MMP2 and MMP9 as well as inhibiting expression of E‐cadherin and β ‐catenin. Abstract : Astrocyte‐elevated gene‐1(AEG‐1) enhanced the capability of ovarian carcinoma cell line (OVCAR3) cells invasion. After infection with AEG‐1 overexpression/negative control lentivirus for 72 h, OVCAR3 cells were collected for transwell assay. Cell lysates were then subjected to western blotting to measure the protein expression of AEG‐1, E‐cadherin, β ‐catenin, matrix metalloproteinase‐2 (MMP2), and matrix metalloproteinase‐9 (MMP9). The results were normalized to GAPDH to correct for loading. Data given are mean ± SD, n = 3. * P < 0.05, ** P < 0.01 versus negative control. (A) AEG‐1 expression, (B) invasion capability and absorbance (OD, optical density) of invaded cell lysates read at 570 nm, (C) MMP2, MMP9, E‐cadherin, and β ‐catenin protein expression of OVCAR3 cells infected with overexpression/negative control lentivirus.